Linking Depressive Symptoms and Cognitive Functioning: The Mediating Role of Leisure Activity - Sharifian, Neika (Neuropsychology, 2019)
OBJECTIVES: Greater depressive symptoms are associated with cognitive decline in older adulthood, but it is not clear what underlying factors drive this association. One behavioral pathway through which depressive symptoms may negatively influence cognitive functioning is through activity engagement. Prior research has independently linked greater depressive symptoms to both lower leisure and physical activity and independently linked both lower leisure and physical activity to lower cognition. Therefore, depressive symptoms may negatively influence cognition by reducing engagement in beneficial leisure and/or physical activities that help to maintain cognition. METHODS. The current study examined associations between depressive symptoms, leisure activity, physical activity, and global cognitive functioning using longitudinal data from the Washington Heights-Inwood Columbia Aging Project (WHICAP; n = 5,458 older adults). A multilevel structural equation model estimated the between-person and within-person effects of depressive symptoms on global cognition through leisure and physical activity. RESULTS. Leisure activity, but not physical activity, mediated the association between depressive symptoms and global cognition between- and within-persons. When individuals reported high depressive symptoms, they also reported fewer leisure activities, which was associated with lower global cognition. CONCLUSION. These findings highlight behavioral pathways through which depressive symptoms may negatively influence cognitive functioning. Findings support the view that perhaps depressive symptoms act as a risk factor for cognitive impairment by reducing leisure activity engagement.